STRATEGI PERENCANAAN PENGELOLAAN PAUD MELALUI KEMAMPUAN KOMPETENSI GURU DI TK TUNAS HARAPAN I WARU - Mahdayani, Pradhita; Mariani, Any; Afendi, H.Ach. Ruslan (TARBAWI:Journal on Islamic Education, 2023)
Nationally, the education system in Indonesia has criteria for its management. Basically, these criteria are prepared to harmonize the quality of management in schools. However, a specific analysis should be carried out at each point to develop the quality of educational services in the schools that provide them. This analysis can actually help develop educational institutions to be more professional and in line with the wishes of society. Educational Management means a collection of activities or efforts carried out by a group of individuals to carry out a set of activities to achieve certain goals. The low skills and professionalism of teaching staff are among the problems that persist to this day. Furthermore, there are pedagogical skills that cannot be marginalized. Pedagogical skills are skills in managing student learning systems, because teachers as learning staff have the function of being motivators, facilitators, engineers, learning boosters and channeling learning motivation for students. Therefore, PAUD management needs to be formed to meet the demands, interests, desires and determine the direction of the school's strategy in achieving educational targets